It's A Battle between Politics the Free Market - Choi, Heeri (2009)
This research contributes to the CEO remuneration literature in the banking sector by examining the issue from the VOC perspective. It compares the two of the most prominent examples of Co-ordinated Market Economy and Liberal Market Economy, the UK and Germany. The research examines the Royal Bank of Scotland and the Deutsche Bank in depth in order to analyse the differences in the banking sector CEO remuneration designs between a CME and a LME.